Imperial Capitals at War: A Comparative Perspective. (1st September 2016) - Gregory, Adrian
Abstract : London was one of six large imperial capitals in Europe (Berlin, Constantinople, Paris, St Petersburg, Vienna) which became focal points of total war during the First World War. In some respects, each of these capitals can be understood as undergoing a form of siege in which the endurance of the population at the heart of the combatant Empires was severely tested. London proved to have important resources which helped it to endure better than some of the others.